Sectoral Balance Sheet Mismatches and Macroeconomic Vulnerabilities in Colombia, 1996-2003 - Lima, Juan Manuel (International Monetary Fund, 2006)
We employ an extended version of the Allen et al. (2002) Balance Sheet Approach to examine macroeconomic vulnerabilities in Colombia between 1996 and 2003, based on an unusually rich data set. We find that vulnerabilities existing prior to Colombia''s 1999 recession-high levels of private debt, a large negative foreign currency position of the corporate sector, and banks'' exposure to stretched households and companies-receded subsequently. New vulnerabilities emerged, however, especially the high level of public debt accumulated until end-2003, and growing exposure of the financial sector to the sovereign